(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the empirical integration of physical material properties, specifically tensile strength, into management accounting models, focusing directly on tool degradation and overall cost efficiency within modern manufacturing environments. While traditional cost accounting systems heavily emphasize standard financial and operational variables, limited academic and practical attention has been given to how intrinsic material characteristics directly influence bottom-line production costs, waste generation, and long-term organizational performance outcomes. To address this critical gap, this study adopts a quantitative research design. Empirical data were collected via structured questionnaires from 210 production engineers, cost accountants, and operations managers working across various manufacturing firms in Nigeria. Both descriptive statistics and multiple regression analysis were employed to rigorously analyze the gathered data. The findings reveal that tensile strength significantly and profoundly influences tool degradation rates (β = 0.72, p < 0.001) and cost efficiency (β = 0.68, p < 0.001). Specifically, processing higher tensile strength materials was strongly associated with accelerated tool wear, elevated maintenance expenses, and reduced cost efficiency when these physical variables are not optimally managed or accounted for during strategic budget planning and forecasting. Consequently, the study concludes that seamlessly integrating key materials science variables into contemporary management accounting frameworks significantly enhances the accuracy of cost predictions and strategic operational decision-making. Ultimately, this paper contributes to interdisciplinary research by successfully linking engineering material properties with traditional cost accounting models. Based on these insights, it recommends that manufacturing firms actively incorporate material-based cost drivers into their performance evaluation systems and comprehensive variance analysis protocols to optimize real-time production workflows, minimize machine downtime, and improve cost control strategies.